2018
DOI: 10.3354/meps12754
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ocean acidification on the settlement and metamorphosis of marine invertebrate and fish larvae: a review

Abstract: Most marine organisms present an indirect lifecycle where a planktonic larval stage reaches competency before settling to the substrate and metamorphosing. Despite the critical importance of these early life history stages, little is known about how global change-related stressors, in particular ocean acidification (OA), affect marine larval settlement and metamorphosis. To date, 48 studies have investigated the effects of OA on larval settlement, focussing mostly on tropical corals (16), echinoderms (11) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
51
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 136 publications
2
51
0
Order By: Relevance
“…Presently, there is limited information on the potential effects of OA on the settlement process 20,47 . Mostly, it has shown that OA has a negative impact on settlement in marine invertebrates, however these conclusions are based on relatively few taxa, and mostly within the Cnidaria and Echinoderm phyla.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Presently, there is limited information on the potential effects of OA on the settlement process 20,47 . Mostly, it has shown that OA has a negative impact on settlement in marine invertebrates, however these conclusions are based on relatively few taxa, and mostly within the Cnidaria and Echinoderm phyla.…”
Section: Discussionmentioning
confidence: 99%
“…While reduced pH has been linked to decreases in the settlement success of vermetids 14 , corals [14][15][16][17][18] , sea stars 11 , and sea urchins 19 , our understanding regarding the OA effects on the settlement processes of marine invertebrates remains limited. In this respect, a recent review by Espinel et al 20 found less than 50 published studies, with the majority indicated neutral or negative changes in settlement under reduced pH. Within these studies, only a small number examined the outcomes of pH induced changes of substrates (biofilms and CCAs) on settlement, and these indicated a reduction in settlement rate in taxa such as coral and sea stars 20 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in chemical cue or cue source can reduce settlement success, such as changes in the algal community and cue integrity reducing coral settlement (Albright , Nagelkerken and Munday , Espinel‐Velasco et al. ).…”
Section: The Impacts Of Climate Change On Larval Transport and Organimentioning
confidence: 99%
“…Larvae with external calcified structures will very likely suffer more extreme physical deformities than non‐calcifying larvae or those with internally buffered calcium structures as pH declines, though increasing evidence points to maladaptive behavior in low pH conditions across a range of taxa which could impact dispersal (Espinel‐Velasco et al. ). Species that release swimming larvae should better adapt to changes in current flow and stratification than free‐spawning species that release passive gametes and embryos, particularly in upwelling regions where offshore and equatorward transport is expected to strengthen.…”
Section: Winners and Losersmentioning
confidence: 99%